Expressive photography : the Shutter Sisters' guide to shooting from the heart - Clark, Tracey, 1967- (Elsevier/Focal Press, 2010)
When a photograph captivates you and stirs your soul, you know it instinctively. You not only see the image, you feel it. But how do you capture shots like that with your own camera? How do you make your photographs worth the proverbial thousand words? From portraits to landscapes, still-lifes to documentary shots, Expressive Photography will not only show you why certain images sing, but will also teach you how to create your own compelling photographic images-one click at a time. Visually stunning, and unique in its collaborative approach, this book brings the spirit of the immensely popula.